OPTIMASI FORMULA DAN STRUKTUR MIKROSKOPIK PASTA BEBAS GLUTEN BERBAHAN DASAR PUREE UBI JALAR UNGU DAN TEPUNG KACANG HIJAU - Ira Mulyawanti; Slamet Budijanto; Sedarnawati Yasni (Agritech, 2016)
The aim of this study was to optimize gluten free pasta formula made from purple sweet potato puree and mung bean flour. Aplication of a mixture design allowed to find the optimal composition to achieve the desirable characteristic. The results showed that the optimal formula was mixture of 45.25% purple sweet potato puree and 51.75% mung bean flour. The characteristics of the chosen formula were springiness of 2.29 mm, 0.38 cohesiveness, cooking loss 17.62%,333.48 ͼHue, Ie   20.59%, and 42.42 mg/L anthocyanin content. Microscopic structure showed that cooked pasta with purple sweet potato puree composition below 50% in the formula had a solid texture appearance.